Prognostic role of excision repair cross complementing-1 and topoisomerase-1 expression in epithelial ovarian cancer - Shih-Chieh Liu; Hao Lin; Chao-Cheng Huang; Chan-Chao Chang Chien; Ching-Chou Tsai; Yu-Che Ou; Hung-Chun Fu; Jacqueline M. Liu; Yen-Ying Ma (Elsevier, 2016)
Objective: Epithelial ovarian cancer is the most lethal gynecologic cancer worldwide and chemoresistance is one of the major causes of treatment failure. We investigated whether ERCC1, TAU, TOPO2A, TOPO1, P53, and C-MYC expression could be used as predictors for treatment outcomes. Materials and methods: Immunohistochemical staining was used to examine the expression of these biomarkers in resected tumor specimens from 38 patients treated in our institute. Clinicopathological data including demographics, staging, histological type, treatment response, expression of the biomarkers, and patient outcomes were analyzed. Results: The median follow-up period was 47.5 months (range, 10-135 months) and the median overall survival was 56.0 months. Patients who did not have expression of ERCC1, and those who had expression of TOPO1 had significantly better overall survival. Cox regression analysis also confirmed that these two biomarkers were significant independent factors predicting survival (ERCC1, hazard ratio 5.51, 95% confidence interval: 2.02-14.00, p = 0.001; TOPO1, hazard ratio 0.22, 95% confidence interval: 0.06-0.77, p = 0.017). Conclusion: We concluded that poor overall survival was significantly associated with positive ERCC1 and negative TOPO1 expression. The results might be the consequence of chemoresistance to platinum and camptothecins, both of which are commonly used regimens in the treatment of epithelial ovarian cancer.